(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In 1900, at the risk of the spread of World War I, the French strengthened the defensive lines on the southwestern coast of France as well as the forts along the Germany-France border. In Vietnam, after occupying all six provinces in the South, in order to protect Sai Gon - the capital of the six provinces from other Western powerhouses, the French built a coastal defensive line stretching from present-day Vung Tau to Can Gio (Sai Gon) and to Can Duoc (Long An) to counter the attacks from the coast to the mainland. Long Huu Island, located between the three rivers of Can Giuoc (Rach Cat), Vam Co and Soai Rap (Nha Be) was chosen as the place to build one of the largest military forts in Indochina at that time - Rach Cat Fort (the French also called it “River Defense System” and “Cap Saint-Jacques"). This is one of the earliest military buildings and the most fortified forts across Indochina, which played a crucial role to the French in Southern Vietnam. In the course of its existence, Rach Cat Fort witnessed many military operations. Currently, despite deteriorated parts, the structure of Rach Cat Fort is still intact. With its unique historical value as well as aesthetic value as an old European-style fort, Rach Cat Fort has been ranked as a National Historic Site and is being developed by local authorities into a tourist attraction that attaches historical relics to eco-tourism.